A review of the Early Mesozoic granitoids in the Qinling Orogen: Implication for gold metallogeny. (1st December 2017) - Yang, Gaoxue; Li, Yongjun; Tong, Lili; Duan, Fenghao; Wang, Zuopeng; Wu, Le; Ning, Wentao
Abstract : The Qinling Orogen is located between the North China and South China blocks, and considered to form by the multiple accretionary processes, being also characterized by development of voluminous magmatic intrusions as well as abundant mineral resources. Here we compile the geological, geochemical and geochronological data of the Early Mesozoic granitoids from the Qingling Orogen and attempt to constrain the Early Mesozoic tectonic evolution and mechanism of gold mineralization in this region. The Early Mesozoic granitoids are most widespread in the Qinling Orogen, especially in western part, and can be classified into S‐, I‐, I‐A‐types, with the I‐type constituting the major variety. The isotopic ages of the three types granitoids are 200–222 Ma, 185–248 Ma, 210–227 Ma, respectively, indicating overlapping ages with a wide span of I‐type granitoids. The S‐, I‐, I‐A‐type granitoids show obvious zonation characteristics, that is the S‐type granitoids only occurred in southern South Qinling Belt, the I‐type granitoids are most widespread in the western Qinling Orogen, and the I‐A‐type granitoids are mainly exposed in the North Qinling Belt. The S‐type granitoids crystallized at relatively low temperature (800–850 °C) and deep‐crustal level (ca. 8 kb) and derived mainly from partial melting of a clay‐poor psammitic source. The I‐type granitoids formed at high temperature (>925 °C) and pressures above the garnet‐in phase boundary (>1.2 GPa) and derived from greywackes and partially igneous source. Moreover, the I‐A‐type granitoids probably derived from distinct sources with sufficient interaction, or common origin but underwent different degrees of crustal contamination, and generated at high temperatures (ca. 950 °C) and low pressures (1.0–0.2 GPa) conditions. These features indicate the Qinling Orogen experienced subduction, syn‐collisional, and post‐collisional during the Early Mesozoic, and also suggest the S‐, I‐, I‐A‐types granitoids underwent an episodic growth documenting the tectonic regime switchover at this stage. The gold deposits in the western Qinling Orogen can be classified as orogenic, Carlin‐type, and Carlin‐like gold deposits with the formation age of Late Triassic. The orogenic and Carlin‐type gold deposits have no genetic relation to granitic magmatism, but the Carlin‐like gold deposits is related to the synchronous magmatism. Combined with regional geology and metallogenic systems, we suggest that the multi‐stage Qinling Orogenesis resulted in the formation of the Early Mesozoic S‐, I‐, I‐A‐type granitoids and different types of gold deposits with some characteristic differences.